A novel miRNA, miR-13664, targets CpCYP314A1 to regulate deltamethrin resistance in Culex pipiens pallens. Issue 2 (3rd July 2018) - Sun, X. H.; Xu, N.; Xu, Y.; Zhou, D.; Sun, Y.; Wang, W. J.; Ma, L.; Zhu, C. L.; Shen, B.
Abstract: Extensive insecticide use has led to the resistance of mosquitoes to these insecticides, posing a major barrier to mosquito control. Previous Solexa high-throughput sequencing of Culex pipiens pallens in the laboratory has revealed that the abundance of a novel microRNA (miRNA), miR-13664, was higher in a deltamethrin-sensitive (DS) strain than a deltamethrin-resistant (DR) strain. Real-time quantitative PCR revealed that the miR-13664 transcript level was lower in the DR strain than in the DS strain. MiR-13664 oversupply in the DR strain increased the susceptibility of these mosquitoes to deltamethrin, whereas inhibition of miR-13664 made the DS strain more resistant to deltamethrin. Results of bioinformatic analysis, quantitative reverse-transcriptase polymerase chain reaction, luciferase assay and miR mimic/inhibitor microinjection revealed CpCYP314A1 to be a target of miR-13664. In addition, downregulation of CpCYP314A1 expression in the DR strain reduced the resistance of mosquitoes to deltamethrin. Taken together, our results indicate that miR-13664 could regulate deltamethrin resistance by interacting with CpCYP314A1, providing new insights into mosquito resistance mechanisms.